Changing the status of the presidency: A comparison of constitutional amendments in South Korea and Turkey - Demirbulak, Hülya Görkem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The aim of this thesis is to plot South Korea and Turkey’s journey towards a constitutional amendment by focusing on their current debates about changing the status of the presidency and to find an answer to the question of whether the intended changes to the respective countries’ constitutions will bring them close to a democratic presidential system. In this context, in this study, a general framework of both countries’ constitutional developments throughout history and the characteristics of their constitutions will be drawn, and the parallelisms in their constitutional histories will be highlighted. Furthermore, the ongoing debates on constitutional revision appertaining to the presidency will be handled with the main matters in question and a comparative assessment will be made within the scope of the similarities and divergences between two countries. As the fundamental legal document defining basic principles of the state, regulating its relationship with the citizens, and reflecting the nation’s history, its future goals, and its view of the world, a constitution constitutes a basis to fully understand a country. For this very reason, by examining the process of South Korean and Turkish constitutional developments throughout history and the current debates on constitutional amendments, this thesis offers the opportunity to thoroughly perceive both countries’ political tradition, to better interpret our modern day, and to make more to-the-point inferences about their futures.
Keywords: Presidents -- Turkey.; Presidents -- Korea (South); Constitutional law -- Turkey.